Effect of Nanoparticle Ag on Wet Accumulator Performance - Januar Widakdo; Febri Rismaningsih (Universitas Negeri Surabaya, 2021)
Energy is the most important and inevitable requirement for humankind. The increasing energy demand has been connected with technological advances and population growth. One of the world's most serious problems is providing sustainable energy. New alternative energy sources and renewable energy technologies have become notable research subjects due to the wide availability of renewable energy sources in the world. However, most renewable energy sources do not provide uninterrupted energy to consumers. This study aims to determine the resistance of the Ag nanoparticle using the UV-Vis spectrophotometer test. It determines the wavelength of Ag absorption, the output voltage characteristics, and the light intensity of the lamp produced from a wet accumulator with the addition of Ag nanoparticles. This research was started by making a solution of Ag nitrate (AgNO3) and a trisodium citrate (Na3C6H5O7) solution, then synthesizing Ag nanoparticles with a concentration of 3 mM, 4 mM, and 5 mM about 2 ml using the bottom-up method and chemical reduction. The results showed that Ag nanoparticles were suitable for use within three days and the Ag absorption wavelength was 328.1 nm. The output voltage on the wet accumulator without adding Ag nanoparticles lasts longer than the accumulator added by Ag nanoparticles. It can be seen clearly from the speed at which the voltage drops. For the light intensity produced by the pure wet accumulator, the H2SO4 solution was measured to be great and went out longer than the wet accumulator added with Ag nanoparticles. This research concluded that Ag nanoparticles with a concentration of 3 mM, 4 mM, and 5 mM in the H2SO4 solution reduce the performance of the wet accumulator.